Breach of the principles of trail and legal rules in insolvency action - Alireza Fasihizadeh; سید حسین اسعدی (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2017)
In Iranian law, the declaration of insolvency is treated as  "insolvency action". Thus, it is reasonable to expect that this action complies with the principles of trial and the legal rules. The fact is that the non-compliance with the fundamental principles is a violation of judgment. However, by examining existing rules and regulation, it becomes clear that in insolvency action proceedings and the decree of insolvency, many principles of trial and general legal rules are not abided by. After a brief introduction of the insolvency action and its governing law, this paper examines the instances of legislator's ignorance and pertinent reasons . In the insolvency action, the legislator has been renounced of the principles such as persons’ insolvency, financial claim disputes, correlation of permission to thing with permission to its concomitants, authority of res judicata, competence of court of domicile, and rules such as kinsman’s liability, privity of judgments, the validity of the judgment and insolvent’s compliance with bankruptcy system.